A new species of hardware. - Sipper, M.
If natural evolution is so successful a designer, why not simulate its workings in an engineering setting, by using a computer to evolve solutions to hard problems. Researchers pursuing this idea in the 1950s and '60s gave birth to the domain of evolutionary computation. Four decades later, the domain is flourishing, both in industry and academia, presenting what may well be a new approach to optimization and problem-solving. Published in 1859, Charles Darwin's ?On the Origin of Species by Means of Natural Selection? shook the foundations of not only science but also society at large. Now with new uses for the evolutionary model coming into being, researchers and scientists are beginning to create hardware that can grow and improve itself over time, evolving steadily as it finds new and better ways to do the tasks it has set before it
Keywords: Evolutionary computation; Hardware; Optimization; Problem-solving.